Drugs in anaesthesia and intensive care - Smith, S. P. (Susan P.); Scarth, Edward; Sasada, M. P. (Martin P.) (Oxford : Oxford University Press, 2011)
Anesthetists can make use of a wide range of drug treatments and this book provides readily available and accessible information on the appropriate drug to use in any given situation.
Previous ed.: published as by Martin Sasada and Susan Smith. 2003.
Includes index.
Description based on print version record.
Includes index.
Keywords: Anesthetics; Critical care medicine